News Brokering, News Placement/Delivery/Contact Services and Public Relations Consultants - Dennis Hinkamp (Journal of Applied Communications, 2003)
Whether you just need a little help, are thinking of large-scale outsourcing, or are just interested in what the competition is doing, you should pay attention to the growing number of services available to communicators.